The Importance of Green Accounting Readiness for Pioneering Companies: A Review Study - Wissam Abdulkadhum Abdulridha (International Journal on Economics, Finance and Sustainable Development, 2026)
The aim of this research is to examine the previous literature on leading companies\' readiness to implement green accounting in the face of environmental pressures and sustainability-driven competition. As regulatory requirements, stakeholder expectations, and market dynamics lean towards responsible business practices, leading companies are increasingly required to incorporate environmental considerations into their strategic and operational frameworks, which reflects their green accounting readiness. Green accounting readiness refers to an organisation\'s readiness to adopt environmental accounting systems, measure and disclose environmental costs, and integrate sustainability indicators into financial and managerial decision-making processes. Results show that leading companies with higher levels of green accounting readiness are more capable of addressing environmental challenges, engaging investors and environmentally-conscious customers, and enabling innovation in volatile markets.